CAR-NK cells derived from cord blood originate mainly from CD56−CD7+CD34−HLA-DR−Lin− NK progenitor cells - Tansri Wibowo; Yosuke Kogue; Shunya Ikeda; Moto Yaga; Mana Tachikawa; Makiko Suga; Shuhei Kida; Kumi Shibata; Kazuhito Tsutsumi; Hiraku Murakami; Yasutaka Ueda; Hisashi Kato; et al. (Molecular Therapy: Methods & Clinical Development)
Cord blood (CB)-derived chimeric antigen receptor (CAR)-natural killer (NK) cells targeting CD19 have been shown to be effective against B cell malignancies. While human CD56+ NK cells can be expanded in vitro, NK cells can also be differentiated from hematopoietic progenitor cells. It is still unclear whether CAR-NK cells originate from mature NK cells or NK progenitor cells in CB. Here, we determined that CAR-NK cells were predominantly derived from CD56− NK progenitor cells. We first found that substantial numbers of CD19 CAR-NK cells were produced from CD56− CB mononuclear cells after in vitro culture for 2 weeks. Single-cell RNA sequencing analysis of CD56−CD3−CD14−CD19− CB mononuclear cells revealed that these cells could be subdivided into three subpopulations based on the expression of CD34 and human leukocyte antigen (HLA)-DR. NK cells originated primarily from CD34−HLA-DR− cells. In addition, among the CD34−HLA-DR− cells, only CD7+ cells could differentiate into NK cells. These results indicate that CD56−CD7+CD34−HLA-DR− lineage marker (Lin)− cells are the major origin of human CB-derived CAR-NK cells, indicating the importance of developing methods to enhance the quality and quantity of NK cells produced from these NK progenitor cells.